Competing commensurate and incommensurate magnetic structures in dhcp Ce/Nd superlattices - Clegg, P; Goff, J; McIntyre, G; Ward, R; Wells, MR (2001)
The chemical and magnetic structure of Cerium/Neodymium superlattices grown by molecular-beam epitaxy have been determined using x-ray and neutron diffraction techniques. The x-ray studies show that both constituents adopt the dhcp structure, and that the stacking sequence is coherent over many bilayer repeats. The dhcp structure remains intact down to T ∼ 2K; these are the first measurements of magnetic ordering in single-crystal dhcp Ce. The magnetic structure of the samples with thicker Nd layers exhibit incommensurate order and ferromagnetism on separate sublattices in a similar manner to Nd under applied pressure. The superlattice with thickest Ce layers has an incommensurate magnetic structure similar to that predicted for bulk dhcp Ce. These two types of magnetic ordering appear to be mutually exclusive.